PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL HYBRID LEARNING MENGGUNAKAN MEDIA SCHOOLOGY PADA MATERI GETARAN, GELOMBANG DAN BUNYI UNTUK KELAS VIII SMP - Dewi, Wini Efrika; Nasir, Muhammad; Syahril, Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The learning device developed is a learning tool based on the Hybrid Learning model using Schoology media on vibrations, waves, and sounds for class VIII SMP, consisting of a Learning Implementation Plan (RPP), Student Worksheets (LKPD), and Learning Outcomes Test. The purpose of this study was to determine the validity of learning tools based on the Hybrid Learning model using Schoology media on vibrations, waves, and sound. This type of research is a research and development (R&D) with a 4D model. The instruments used were the RPP validation assessment sheet, LKPD, and the Learning Outcomes Test which were used by the validator to assess learning tools. Data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. Based on the results of the validity data analysis, it was obtained that the average validity of the lesson plans at the first, second, third and fourth meetings was 3.51, 3.48, 3.45, and 3.42 with the very high category (ST), the average the validity of LKPD 1, 2, 3, and 4 of 3.45, 3.40, 3.45, and 3.40 in the high category (ST), and the average validity of the Learning Outcomes Test was 3.52 with the very category height (ST). Thus, the learning device based on the Hybrid Learning model using the developed Schoology media is declared valid and suitable for use by class VIII junior high school students on vibration, waves and sound.Keywords: Device Development, Hybrid Learning Using Schoology Media, Vibration, Waves and Sounds.